Peran Orang Tua dan Guru Aqidah Akhlak Dalam Pendidikan Iman di MTSS Yati Kamang Mudik Kabupaten Agam - Aulia Rahmi Shakila; Alimir A; Arifmiboy A; Fauzan F (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine how the role of parents and Akidah Akhlak teachers in faith education at MTsS Yati Kamang Mudik Agam Regency. The method used is descriptive qualitative with data collected through observation, interviews, and documentation. The results showed that the parents and teachers of akidah akhlak in students' faith education at MTsS Yati Kamang Mudik Agam Regency, so the main conclusion of this study can be drawn is The role of parents and teachers in students' faith education shows that both play an important role in shaping and developing students' spirituality and morality. Parents are identified as the creators of a supportive environment. Despite being faced with various challenges, Meanwhile, the role of teachers in faith and morals is not only limited to teaching religious materials, but also includes the role of classroom manager, guide, motivator, and mediator. Through this approach, teachers not only improve students' understanding of religious principles, but also help them apply those values in their daily lives. Thus, the main conclusion of this study is that the role of parents and teachers in students' faith education at MTsS Yati Kamang Mudik Agam Regency is very important and complementary. Both have responsibilities in shaping and developing students' spirituality and morality through an integrated and sustainable approach.